2003
DOI: 10.1890/02-0208
|View full text |Cite
|
Sign up to set email alerts
|

Search Strategies of a Pursuit-Diving Marine Bird and the Persistence of Prey Patches

Abstract: Abstract. We explored foraging strategies used by marine animals to search for prey by examining the relative importance of information exchange and memory in a cold ocean environment from 1998 to 2000. Recent technological advances have increased our knowledge of the foraging patterns of marine predators, but few of these studies have concurrently measured prey distribution and behavior. We quantified the arrival and departure behavior of a pursuit-diving, colonial seabird, the Common Murre, Uria aalge, at tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
92
0
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 133 publications
(99 citation statements)
references
References 61 publications
6
92
0
1
Order By: Relevance
“…This assumption 545 appears valid in some low latitude breeders which forage in oceanic waters (Weimerskirch 2007, 546 Weimerskirch et al 2010). However, in temperate, polar and neritic habitats prey patches may be 547 less variable, perhaps persisting across years (Davoren et al 2003). In accordance with the 548 WSLS hypothesis, we found that spatial consistency in gannets was not absolute (population 549 mean < 0.6; Fig.…”
Section: Covariance In Different Measures Of Consistency 488supporting
confidence: 72%
“…This assumption 545 appears valid in some low latitude breeders which forage in oceanic waters (Weimerskirch 2007, 546 Weimerskirch et al 2010). However, in temperate, polar and neritic habitats prey patches may be 547 less variable, perhaps persisting across years (Davoren et al 2003). In accordance with the 548 WSLS hypothesis, we found that spatial consistency in gannets was not absolute (population 549 mean < 0.6; Fig.…”
Section: Covariance In Different Measures Of Consistency 488supporting
confidence: 72%
“…In the case of Lys Island, where the availability of prey may be hard to predict, colonialism may increase the breeding success of individuals. However, recent results do not support the information centre hypothesis (Davoren et al 2003). It has even been demonstrated that the size of the colony is negatively correlated to the foraging activity of individuals (Lewis et al 2001, Ainley et al 2003.…”
Section: Non-seasonality Of Lys Island Breeding Regimementioning
confidence: 84%
“…Other factors that affect the coherence of predators and prey include prey abundance (Skov et al 2000, Davoren & Montevecchi 2003, Vlietstra 2005) and the spatial resolution of predator−prey integration (Schneider & Piatt 1986, Mehlum et al 1999, Fauchald et al 2000. Seabirds and prey can be more tightly coupled when prey and seabird abundance is relatively high (Mehlum et al 1999, Fauchald et al 2000, although exceptions do exist, i.e.…”
Section: Seabird−prey Associationsmentioning
confidence: 99%